Princípios de usabilidade na Biblioteconomia: parâmetros para análise em Sistemas de Bibliotecas - AMARAL, Camila Chaves (2023)
It presents usability evaluations in library systems, analyzing scientific papers published between 2016 and 2020, indexed in a Brazilian information science electronic bibliography (Base de Dados em Ciência da Informação - BRAPCI). The main objective is to contribute with debate about usability in Librarianships information systems. The specific objectives are: come up with theoretical bases of usability in information systems; identify works that analyzed usability in library systems; and indicate the most applied usability evaluative methods. The main problematic question is how studies in usability can contribute with information system evaluations in Librarianship and Librarian Science. It is a exploratory research with a quali-quantitative approach that uses content analysis technique and, as data collection procedure, bibliographical and documental approach. The results reveal that there were the highest number of usability evaluations in library systems between 2016 and 2017, and the systems that were most evaluated were the institutional repository and the online scientific journal. It is concluded the application of the Empirical Model and the User Method, as well as the adoption of Evaluation Techniques as profile questionnaires (Prospective Technique), interaction tests (Objective-Empirical Technique) and Nielsen's heuristics (Predictive-Analytical Technique) were the most preferred methods for usability evaluation in library systems. Finally, Usability in the area of Librarianship expands the debate on the easeful use of informational and technological resources by users, given that information is an indispensable component for the development of contemporary society.